Kewenangan Dokter Spesialis Dalam Melakukan Tindakan Medis Di Klinik Utama Rawat Inap - Pamuji, Ns; Huda, M Khoirul (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2019)
Every citizens have the same right to access the health service in the form of promotive, preventive, curative, and rehabilitative which facilities are held by the government, the local government, and the society including the primary clinic. A specialist doctor in the inpatient primary clinic has atributive, mandatory, and delegative authority based on the education standard, competency, profesional standard, and operational procedure standard. The primary clinic can conduct the mild and moderate surgery with general anesthesia. However, there is a contradiction between two regulations that later limits the authority of the specialist doctor and the anesthesia doctor to conduct the surgery.  A specialist doctor in carrying out their authority should consider the operational standard, informed consent, ethical code, and the hospital by law.  Along with the authority, the doctor also has a huge responsibility to treat the patients based on the procedure both legally and ethically as detemined. The previous regulation, Health Ministry Regulation of the Republic of Indonesia article 9 year 2014 about clinic, has not enacted firmly about the specialist doctor’s authority in the inpatient primary clinic. The specialist doctors have legal responsibility, profesional responsibility, ethical and discipline responsibility, criminal law responsibility, civil law responsibility, and administrative law responsibility Therefore, we recommend to conduct a judicial review on Health Ministry Regulation of the Republic of Indonesia article 9 year 2014 about the specialist doctor’s authority.